Vitamin D and Selenium: Review of Clinical Trials of Synergistic Effects on Thyroid Antibody Levels and Disease Progression in Hashimoto’s Thyroiditis - Agnieszka Starzyk; Piotr Charzewski (Quality in Sport)
Introduction: Hashimoto's Thyroiditis (HT) is a common autoimmune thyroid disorder caused by genetic predispositions and environmental factors, such as iodine imbalance, selenium deficiency, and stress. It is characterized by chronic lymphocytic infiltration of the thyroid gland, leading to hypothyroidism and the production of thyroid-specific autoantibodies, particularly anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-TG) antibodies.